Isolasi Identifikasi Bakteri Penghasil Xilanase serta Karakterisasi Enzimnya - Nur Richana; Tun T. Irawadi; Anwar Nur; Khaswar Syamsu (Jurnal AgroBiogen, 2008)
Xylanase is an extracellular enzyme produced bymicroorganisms. This enzyme is able to hydrolise xylane(hemicellulose) to produce xylooligosaccharide and xylose.Thermoalkaliphilic xylanase is an agent that can be used asa substitute in the pulp whitening process instead of chlorine.A study was done to isolate, identificate of bacteria andcharacterize xylanase. The isolation of xylanase producingbacteria has been done from soil and waste of starch industry.Colonies which produced clearing zone were presumedas xylanolytic bacteria and chosen for further screening.Identification of potential isolate in xylanase production wasdone using 16S ribosomal RNA sequencing. Isolate Bacilluspumilus RXA-III5 originated from lime or alkaline soil wasmore potential isolate in xylanase production than other 24isolates. Precipitation of xylanase, that was done usingammonium sulphate followed by dialyzes produced xylanaseof a higher specific activity (267.1 U.mg-1) than that usingacetone (131.1 U.mg-1) and ethanol (186.65 U.mg-1). Xylanasewas done at purification produced three fractions of xylanase.Xylanase characteristics consist of pH and temperature(9 and 50oC), Km and Vmaks value 6 mg.ml-1 and 0.2mol.minute-1, respectively. The Fe2+ was the strongest activetorand Mg2+ was the strongest inhibitor activity. This enzymewas detected as a cellulose-free xylanase. Xylanase is aprospective agent for bio-bleaching of paper.